Pemberdayaan UMKM Djasmine Bordir: Peningkatan Kapasitas Produksi dan Pemasaran Digital - Prasetyani, Dwi; Honggowati, Setianingtyas; Hartoko, Sri; Rahmawati , Rahmawati; Murni, Sri; M. Rudianto, M; Mulyani, Sri (Jurnal Inovasi Pengabdian Masyarakat, 2025)
Djasmine Bordir MSME, located in Kudus, faces several major challenges in business development, particularly in terms of production capacity and marketing. The problems encountered include a shortage of skilled labor, manual production processes that result in low efficiency and production capacity, as well as conventional marketing strategies that limit market reach. To address these issues, this community service activity aims to enhance the competitiveness of Djasmine Bordir MSME by providing computerized embroidery machines and digital marketing training. The methods implemented in this program include training on the use of computerized embroidery machines to improve workforce skills, intensive assistance during the production process, as well as training and mentoring in digital marketing to enable products to reach a wider market. In addition, regular monitoring and evaluation are conducted at each stage to ensure the effectiveness of the program. The expected outcomes of this activity are increased production capacity, improved production efficiency, and expanded market reach through the utilization of digital technology. With this intervention, it is hoped that there will be an increase in turnover, operational efficiency, and the sustainability of Djasmine Bordir MSME, thereby contributing to local economic growth and community empowerment.